Digitization of Employee Attendance through a Web Based Electronic Attendance System at PT Dupoin Palembang Branch - Muhammad caesar; Dedi Haryanto; Apriansyah (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
PT DUPOIN Palembang Branch is one of the companies experiencing efficiency problems in its employee attendance management system. Currently, attendance recording is still carried out manually using paper-based documents stored in filing cabinets. Along with the increasing number of employees and operational activities, this conventional system has caused various issues, such as slow data recapitulation, frequent recording errors, and difficulties in conducting periodic attendance analysis. Moreover, the absence of an integrated attendance history makes it challenging for management to objectively evaluate employee discipline and performance. This study aims to address these issues by implementing a web-based electronic attendance system as a digitalization effort in human resource management. The proposed system enables real-time attendance monitoring, online access to attendance reports, and more transparent and accountable data management. Features such as user authentication, access control, automated reporting, and cloud-based data storage provide significant advantages over manual systems. In addition, the system supports flexible work models, including remote and hybrid working arrangements, while maintaining data accuracy and minimizing fraud through location- and time-based validation. The implementation of this system is expected to improve administrative efficiency, enhance decision-making, and support a more adaptive and productive work environment.